2020
DOI: 10.1167/tvst.9.6.18
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Esterification on Retinal Pigment Epithelial Uptake Using Rhodamine B Derivatives

Abstract: This study investigated the effects of esterification and increased lipophilicity on cellular penetration, accumulation and retention in ARPE-19-nic cells using ester functionalized rhodamine B dyes. Methods: Rhodamine B was esterified to generate four dyes with increasing lipophilicity. Cellular uptake, retention and mitochondrial localization were investigated in vitro using ARPE-19-nic cells using direct intracellular and extracellular and mitochondrial fluorescence quantitation, confocal and high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Thus, when explaining the different cytotoxic activities of the analyzed compounds, the size, structure, and ring geometry of the attached amine should be taken into account. There have also been reports in the literature that esterification can increase bioavailability and cellular penetration [21][22][23][24]. In addition, other in vitro studies have shown that amidine analogs of melphalan reduce the number of estrogen receptor-positive and estrogen receptor-free breast cancer cells [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when explaining the different cytotoxic activities of the analyzed compounds, the size, structure, and ring geometry of the attached amine should be taken into account. There have also been reports in the literature that esterification can increase bioavailability and cellular penetration [21][22][23][24]. In addition, other in vitro studies have shown that amidine analogs of melphalan reduce the number of estrogen receptor-positive and estrogen receptor-free breast cancer cells [25,26].…”
Section: Discussionmentioning
confidence: 99%